Idiopathic scrotal calcinosis – a case report - Khan, Muhammad Mehraiz; Mirza, Zeeshan Rashid; Cheema, Faisal Ehsan; Rafia Shahzad (Journal of the Pakistan Medical Association, 2023)
Idiopathic scrotal calcinosis is formation of calcium deposits in the dermal layers of the scrotum. It results in the formation of single or multiple nodular calcifications that vary in size and number. First reported in 1883, this condition is common in the third decade of life. The presenting complaints range from disfigurement to itching, leading to decreased quality of life. The diagnosis is usually made on a clinical basis and can be confirmed by the histopathology of the excised nodules. Surgical removal of the nodules is the generally recommended treatment. The surgery aims to eradicate the nodules leaving the scrotal skin enough for scrotoplasty. We present a case of idiopathic scrotal calcinosis in a 37 years old male who came for radiological examination. Keywords: Calcinosis, scrotum, calcium, pruritus.